Healthfulness of Fast-Food and Full-Service Restaurants in 16 Georgia Counties after Mandatory Menu Labeling - Janani Rajbhandari-Thapa; Donglan Zhang; Nicole Katapodis; Dana Alvin; Melanie Andrews (Journal of the Georgia Public Health Association, 2022)
Background: Despite that the effect of menu labeling on consumer choices has been studied, there are gaps in the research on the healthfulness of the restaurant food environment post-mandatory menu labeling, specifically in the Southern United States. This study aims to assess the healthfulness of fast-food and full-service chain restaurant environments after compliance with mandatory menu labeling.